Green roof concept analysis: a comparative study of urban farming practice in cities / Nur Hayati Hashim, Nur Huzeima Mohd Hussain and Asmat Ismail - Hashim, Nur Hayati; Mohd Hussain, Nur Huzeima; Ismail, Asmat (Universiti Teknologi MARA, Perak, 2020)
The emergence of urban farming mainly for food production is one initiative in developing a sustainable environment. This paper presents a brief conceptual review of the ideas, issues and imperatives in implementing urban farming on the rooftop areas. The concern is to investigate an alternative way for urban dwellers to achieve resilience through urban farming - the review is based on the theoretical background and concepts of the relevant constraints taken from various established references. The method adopts comparatives analysis explicitly through established texts and secondary data taken from previous cases. The significant examples include; (i) green roof as rooftop farming in ensuring food security and reduce carbon footprint in Singapore; (ii) urban farming as a culture in emphasizing the domestic food production and consumption in Japan; (iii) rooftop urban farming in fresh urban food production in USA; and (iv) rooftop is effective as edible landscape and not only serve for visual purpose only in Thailand. These cases will lead to localize the concept of rooftop urban farming. There also will be a strategy for the greening of the cities by intensifying urban farming. This paper envisions to extend and establish the conceptual discourse for implementing urban farming on the rooftop areas in Malaysia.